Geographical patterns of parasite infracommunities in the rough scad, trachurus lathami Nichols, in the southwestern Atlantic ocean - Braicovich, Paola Elizabeth (2012)
We assessed temporal variability in parasite infections of rough scad Trachurus lathami in 3 samples from Miramar (MI) in 2008, separated by periods of 1 mo, and 2 samples from Villa Gesell (VG), 1 each in 2008 and 2009 (Buenos Aires Province, Argentina), respectively. A sample was also obtained from Cabo Frio (CF) (Brazil) in 2009 to compare differences in parasite communities between fish from this locality and each Argentinean locality. All rough scad were parasitized by at least 1 of 27 parasite species. Similarity-based multivariate analysis revealed significant differences between localities, but temporal homogeneity in each Argentinean locality. Overall, prevalence and abundance of parasite species were most similar between samples from MI and VG, while the greatest differences occurred between samples from MI and CF. A canonical analysis of principal coordinates showed significant differences among samples. Grillotia carvajalregorum was the most important species in determining the position of Argentinean samples, especially those from MI, Ectenurus virgulus, Raphidascaris sp., and Hysterothylacium sp. were the most important species related to fish from CF. The parasite assemblage of T. lathami showed a notable temporal persistence within the same locality and a high variability at the spatial scale, suggesting the existence of 3 independent stocks of T. lathami in South Atlantic waters.